Neoadjuvant therapy for resectable pancreatic cancer - Rahman, Sheikh Hasibur; Urquhart, Robin; Molinari, Michele (World journal of gastrointestinal oncology, 2017)
The use of neoadjuvant therapies has played a major role for borderline resectable and locally advanced pancreatic cancers(PCs). For this group of patients, preoperative chemotherapy or chemoradiation has increased the likelihood of surgery with negative resection margins and overall survival. On the other hand, for patients with resectable PC, the main rationale for neoadjuvant therapy is that the overall survival with current strategies is unsatisfactory. There is a consensus that we need new treatments to improve the overall survival and quality of life of patients with PC. However, without strong scientific evidence supporting the theoretical advantages of neoadjuvant therapies, these potential benefits might turn out not to be worth the risk of tumors progression while waiting for surgery. The focus of this paper is to provide the readers an overview of the most recent evidence on this subject.